Mauritania Economic Update, July 2014 - Mele, Gianluca (World Bank Group, Washington, DC, 2014)
Real gross domestic product (GDP) expanded by 6.7 percent in 2013, a modest deceleration from the 7 percent recorded in the previous year, but well above the average 4.9 percent rate of growth recorded over the last ten years. The economy benefited from strong growth in the agriculture (rebounding from last year's drought), mining and services sectors, which largely offset weaker activity in fishing activity. A continuation of these relatively robust growth conditions is anticipated over the next three years, as the economy benefits from a continued expansion of mining output, particularly of iron ore. In 2015 the largest contributions to growth are projected to come from trade, livestock and iron, although the fast growing sub-sectors are expected to be copper, gold and manufacturing. Following the macroeconomic analysis (section B) this economic update includes a section on partnership agreements and sectoral developments (section C), as well as two special sections on inclusive growth, wealth accounting (section D), economic diversification and efficiency in natural resource use (section E). Section F concludes the document with some indicative policy recommendations.